Fracture criterion and control plan on CO2 pipelines: Theory analysis and full-bore rupture (FBR) experimental study. (March 2021) - Guo, Xiaolu; Xu, Shuangqing; Chen, Gaojun; Yan, Xingqing; Cao, Qi
Abstract: Pressurized pipelines are the most reliable and cost-effective option for the long-distance transportation of CO2 from an emitter to an onshore storage site. Propagating or unstable factures are considered catastrophic pipeline failures, resulting in a massive escape of inventory within a short period of time. The decompression curve for CO2 exhibits a large drop in decompression wave speed at the phase transition pressure, leading to a higher driving force for crack propagation. The study of fracture control plans is very important for assessing the possibility of fracture propagation and preventing unstable fracturing along CO2 pipelines. Three full-bore rupture (FBR) experiments were performed using an industrial-scale (258 m long, 233 mm inner diameter) CO2 pipeline with initial CO2 states of gaseous, dense and supercritical phases, respectively. The relation between the decompression velocity and the pipeline fracture propagation velocity was analyzed during the process of buried CO2 pipeline release. A fracture propagation criterion was established for the buried CO2 pipeline. For the gaseous CO2 leakage, the pressure plateau corresponding to the decompression wave velocity only appeared near the closed end of the pipeline. For the dense CO2 leakage, the pressure plateau corresponding to the decompression wave velocity was observed near the saturation pressure after rapid decompression. For the supercritical CO2 leakage, the pressure plateau corresponding to the decompression wave velocity was observed in the stage when the supercritical CO2 transformed into the two phases of gas and liquid. Compared with the gaseous and dense CO2, for the supercritical CO2, the initial decompression wave velocity was the smallest, and the requirement of the pipeline safety factor was the highest. Highlights: Three full-bore rupture experiments were performed. The fracture criterion of buried CO2 pipeline were established.